A multi-leader-follower game for energy demand-side management. (1st February 2023) - Aussel, Didier; Lepaul, Sébastien; von Niederhäusern, Léonard
Abstract : A multi-leader-follower game (MLFG) corresponds to a bilevel problem in which the upper level and the lower level are defined by Nash non-cooperative competition among the players acting at the upper level (the leaders) and, at the same time, among the ones acting at the lower level (the followers). MLFGs are known to be complex problems, but they also provide perfect models to describe hierarchical interactions among various actors of real-life problems. In this work, we focus on a class of MLFGs modelling the implementation of demand-side management in an electricity market through price incentives, leading to the so-called Bilevel Demand-Side Management problem (BDSM) . Our aim is to propose some innovative reformulations/numerical approaches to efficiently tackle this difficult problem. Our methodology is based on the selection of specific Nash equilibria of the lower level through a precise analysis of the intrinsic characteristics of (BDSM).